Provider communication and HPV vaccine uptake: A meta-analysis and systematic review - Oh, N. Loren; Biddell, Caitlin B.; Rhodes, Blythe E.; Brewer, Noel T. (Preventive medicine, 2021)
Provider communication can be critically important to families as they consider HPV vaccination. We sought to characterize the association of provider communication and HPV vaccine uptake, and when communication better motivates vaccination. We searched four databases for studies published between 2006 and 2019. Eligible studies examined health care provider communication (defined as recommendation or discussion) and HPV vaccine uptake (defined as initiation, completion, or follow-through) in the US. Two coders independently identified eligible studies and coded effect sizes and study characteristics. We pooled effect sizes using random-effects meta-analysis. We identified 59 eligible studies of 265,083 patients. Receiving a provider recommendation was associated with higher HPV vaccine initiation (pooled OR = 10.1, 95% CI: 7.6–13.4). HPV vaccine initiation was 24% for patients without and 60% for patients with a provider recommendation. The pooled effect size for provider recommendation and initiation was smaller for probability samples, clinical records, and NIS-Teen (all p < 0.002). Recommendations were equally effective for males and females, for different patient ages, and over time. Provider recommendation was also associated with higher HPV vaccine series completion and follow-through. Provider discussion was similarly associated with higher HPV vaccine initiation (OR = 12.4, 95% CI: 6.3–24.3). In summary, provider communication was robustly associated with HPV vaccination initiation, completion, and follow-through. These findings suggest that US public health efforts to increase HPV vaccine coverage should continue to emphasize provider communication. •Provider recommendation has a robust association with HPV vaccination initiation, completion, and follow-through.•A greater percentage of patients initiated HPV vaccination when receiving a provider recommendation.•HPV vaccination uptake with provider recommendation occurs in females and males across ages and over time.•Provider discussion has a similarly robust association with HPV vaccination initiation compared to provider recommendation.•Provider communication should be an essential part of efforts to increase HPV vaccination coverage in the United States.